Cooperative Question Answering Semantic Web - Melo, Dora (2011)
In this paper we propose a Cooperative Question Answering System that takes as input queries expressed in natural language and is able to return a cooperative answer obtained from resources in the Semantic Web, more specifically DBpedia represented in OWL/RDF as knowledge base and WordNet to build similar questions. Our system resorts to ontologies not only for reasoning but also to find answers and is independent of prior knowledge of the semantic resources by the user. The natural language question is translated into its semantic representation and then answered by consulting the semantics information sources. If there are multiple answers to the question posed (or to the similar questions for which DBpedia contains answers), they will be grouped according to their semantic meaning, providing a more cooperative and clean answer to the user.